Penyelesaian Sengketa Kebocoran Data Pribadi Nasabah Bank Melalui Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan (LAPS SJK) - Alif Rizqi Ramadhan; Albertus Sentot Sudarwanto (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The advancement of technology has brought significant changes in the banking sector, posing new challenges related to the protection of customers' personal data. Data breaches can harm customers and undermine public trust in financial institutions. To address disputes related to data breaches, the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK) becomes a relevant choice. This study uses a normative legal approach to analyze the legal framework and dispute resolution procedures applied by LAPS SJK. The results show that LAPS SJK prioritizes the principles of accessibility, independence, fairness, efficiency, and effectiveness in dispute resolution. The methods of dispute resolution offered include mediation, arbitration, and binding opinions. Through LAPS SJK, customers can obtain fair, fast, and affordable dispute resolution without having to go through conventional judicial processes. Therefore, LAPS SJK plays a crucial role in protecting customers' rights and maintaining public trust in the banking sector.